2013
DOI: 10.2196/jmir.2702
|View full text |Cite
|
Sign up to set email alerts
|

Physician Choice Making and Characteristics Associated With Using Physician-Rating Websites: Cross-Sectional Study

Abstract: BackgroundOver the past decade, physician-rating websites have been gaining attention in scientific literature and in the media. However, little knowledge is available about the awareness and the impact of using such sites on health care professionals. It also remains unclear what key predictors are associated with the knowledge and the use of physician-rating websites.ObjectiveTo estimate the current level of awareness and use of physician-rating websites in Germany and to determine their impact on physician … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
183
5
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(212 citation statements)
references
References 44 publications
(57 reference statements)
12
183
5
12
Order By: Relevance
“…30 It has been said that one' s "online reputation" is now just as important as one' s reputation among the general community, 31 and the results from our 3 vignettes seem to support that perspective. Regardless of whether respondents had viewed physician ratings in the past, and independent of the respondents' individual characteristics (eg, age, gender, educational level), both positive and negative online ratings strongly influenced the likelihood of selecting a child's physician recommended by a neighbor.…”
Section: -33mentioning
confidence: 59%
See 1 more Smart Citation
“…30 It has been said that one' s "online reputation" is now just as important as one' s reputation among the general community, 31 and the results from our 3 vignettes seem to support that perspective. Regardless of whether respondents had viewed physician ratings in the past, and independent of the respondents' individual characteristics (eg, age, gender, educational level), both positive and negative online ratings strongly influenced the likelihood of selecting a child's physician recommended by a neighbor.…”
Section: -33mentioning
confidence: 59%
“…[27][28][29][30] Our national study focused on parents seeking a physician for their children, whereas other studies have not made that distinction. About three-quarters (74%) of parents in our survey were aware of rating sites for physicians, and more than one-quarter (28%) had sought information on physician ratings for their children within the past year.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a survey of 1000 surgical patients at Mayo clinic found that 81% would seek consultation from a physician based on positive reviews alone, and 77% would not seek consultation from a physician based solely on negative reviews [8]. Similar data has been reported in Europe [9]. Because of the strong impact of online ratings on healthcare consumers' choices, it may be reasonable to use them as a proxy measure "community reputation," if this is defined as how likely a patient is to choose to consult with a given practice based on community opinions.…”
Section: Introductionmentioning
confidence: 55%
“…A 2013 study conducted in Germany found 32.09% (483/1505) of individuals were aware of physician-rating websites. The same German study found 65.35% (248/381) chose a physician based on their online ratings and 52.23% (199/381) decided against a doctor due to their ratings [10]. With increasing public awareness and usage of feedback websites, the presence and perceptions of physicians online play an important role in attaining and retaining patients [3].…”
Section: Discussionmentioning
confidence: 99%